Teacher Leadership in Indonesian Schools: Opportunities, Supports, and Barriers through the Driving Teacher Program - Duwi Wahdany; Dwi Esti Andriani (STAI Hubbulwathan Duri, 2025)
Teacher leadership is increasingly recognized as a catalyst for school improvement and educational reform. In Indonesia, the Driving Teacher Program (Program Guru Penggerak) was launched to foster teacher leadership through structured professional development. However, empirical insights into how such leadership is enacted and supported remain limited. This qualitative study employed a phenomenological approach to explore the lived experiences of nine alumni from the 5th and 7th cohorts of the Driving Teacher Program in Yogyakarta. Data were collected through semi-structured interviews and analyzed using thematic analysis following Braun and Clarke’s framework. The findings reveal three overarching themes: (1) Opportunities for leadership development include assuming formal roles, engaging in training, leading professional communities, sharing best practices, and participating in curriculum and research initiatives; (2) Key supports include principal encouragement, collegial collaboration, and a school culture conducive to innovation; and (3) Barriers include time constraints, communication challenges, peer resistance, workload, and seniority-based hierarchies. The study underscores the importance of systemic and contextual factors in shaping teacher leadership trajectories. It highlights the need for sustainable support structures, collaborative school cultures, and adaptive leadership roles. While the Driving Teacher Program provides a strong foundation, its impact depends on how leadership is interpreted and enacted at the school level.